Compact hydraulic press load lifter / Nurul Ain Ahmad Shahril ... [et al.] - Ahmad Shahril, Nurul Ain; Abdul Majid, Noryasmin; Abdullah, Nor Syahmi Aizat; Yusoff Cheah, Muhammad Redha Yassin; Zaidi, Muhammad Zulfadhli (2019)
MiLiC Sdn Bhd offers mini crane products and services for our customers, providing variety functions of the mini crane that gives high satisfaction of consumers. Our client is customers identifying as middle and low class who want consume product with affordable price. We are also targeting rural people because we have delivery services of our product to customers place. Across Johor and Johor Bahru particularly the MiLiC Sdn Bhd business has been seen an explosion of growth over the year. Johor Bahru is an area that we think the most suitable place to run our business that can attract our customers which have small company which can use this for their own usage. MiLiC Shd Bhd marketing strategy is emphasize the quality and price of our products and services. We offer the affordable price to our customer so they can have it for their own. Thus, we develop our marketing strategy that give attraction to our customers to come to our shop.